2010
DOI: 10.1002/qua.22946
|View full text |Cite
|
Sign up to set email alerts
|

Classification of partially reflecting surfaces using photodetached electron spectrum

Abstract: Photodetachment spectra of H− near a partially reflecting surface is investigated by closed orbit theory. A reflection parameter K is introduced for the analysis of the photodetached-electron spectrum. Factor K controls the spectra on the screen and strongly depends on the surface properties of a material. This parameter can effectively be used for the classification of surfaces using photodetachment microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…[2][3][4][5][6] The study of behavior of the detached electron from a negative ion lying in magnetic field or electric field or near a metallic surface is important in understanding of the physics of negative ions as well as surfaces. 7) The photodetachment process is strongly affected by the presence of external fields and surfaces. It has been observed that static electric field stimulates oscillations in the photodetachment cross section of H À .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] The study of behavior of the detached electron from a negative ion lying in magnetic field or electric field or near a metallic surface is important in understanding of the physics of negative ions as well as surfaces. 7) The photodetachment process is strongly affected by the presence of external fields and surfaces. It has been observed that static electric field stimulates oscillations in the photodetachment cross section of H À .…”
Section: Introductionmentioning
confidence: 99%
“…At about the same time, De‐Hua et al successfully applied closed orbit theory to analyze photodetachment of normalH near two parallel elastic interfaces. Afaq and Iftikhar have studied the photodetachment of normalH near inelastic surfaces using closed‐orbit theory by introducing a new parameter called reflection parameter to account for inelastic behavior of the surfaces. Photodetachment cross section of normalH near hard spherical surfaces has also been investigated by theoretical imaging method .…”
Section: Introductionmentioning
confidence: 99%
“…Being an innovative testing ground for many fundamental phenomenon in the fields of physics, chemistry, biology, and material science and technological applications, the photodetachment of negative ions near different interfaces has received a considerable attention both by theories and experiments in recent years. [7][8][9][10][11][12][13][14][15][16][17] Presence of elastic and inelastic surfaces modifies the photodetachment cross section and the resonance life time of an adsorbed ion due to change in the barrier penetrability of photoelectrons. [18,20] First, in 2006, Yang et al [7] derived a theoretical formula for the photodetachment cross section of H 2 near an elastic surface for the z-polarized laser light.…”
Section: Introductionmentioning
confidence: 99%
“…The 𝐾 can be used similarly to Ref. [12] for the classification of different types of reflecting surfaces, where the radius of curvature may be used to reveal minor details of the surfaces.…”
mentioning
confidence: 99%
“…The value of 𝐾 depends upon the nature of the surface and varies from 0 to 1. [12] When 𝐾 = 1 and 𝑟 𝑐 ≫ 𝑑, Eq. ( 11) reduces to the results of a perfectly reflecting plane wall case, as reported in Ref.…”
mentioning
confidence: 99%